Partial least square structural equation modelling (PLS-SEM) in knowledge management studies: Knowledge sharing in virtual communities - Muhammad Ashraf, Fauzi (The University of Hong Kong, 2022)
Partial least square structural equation modelling (PLS-SEM) has been used as a popular research method in various disciplines, including knowledge management (KM). This paper reviews how PLS-SEM has been used in KM studies, which focus on knowledge sharing in the context of virtual community (VC). The review includes 30 articles published from 2007 to 2019. The review discusses the reasons behind the use of the PLS-SEM, data and model characteristics, evaluation of measurement, and structural model in these studies. This paper also provides guidance on how PLS-SEM can be better used and applied in future research.